Review of leafhopper genus Dwightla McKamey (Hemiptera: Cicadellidae: Deltocephalinae: Selenocephalini) with description of a new species from Central African Republic - Xu, Deliang; Zhang, Yalin (Zootaxa, 2019)
The leafhopper genus Dwightla McKamey (Hemiptera: Cicadellidae: Deltocephalinae: Selenocephalini) is reviewed with description of a new species, Dwightla lancea sp. nov., from Central African Republic. An updated checklist with distribution and a key to males of this genus from Afrotropical Region are also provided.